Politics of land reforms in India - "Thakur, D." (New Delhi, 1989)
he first systematic and empirical attempt to study the political manoeuvres and built-in-depressors relating to land reforms in the post-independent India, this book analyses in depth the various factors that were responsible for the failure of agrarian measures in the country, particularly in the state of Bihar. It probes into the specific role of certain Congressmen and ex-landlords who were expected to enact land reform measures and implement them. It also reveals behind the curtain manoeuvres of the political leadership and the inner-party manipulations which stalled the actual implementation of land re forms in Bihar. Moveover, it exposes the inconsistent and sometimes contradictory approach of the opposition parties of both left and right pursuasions towards this burning problem of land reforms. It deals with Bhoodan and Gramdan Movements to find out their efficacy towards the solution of agrarian problem. This book revolves round the whole politics of land reforms in its different facets.
Keywords: Land reform